Novel gene PUS3 c.A212G mutation in Ukrainian family with intellectual disability - Gulkovskyi, R.V.; Chernushyn, S.Y.; Livshits, L.A. (Вiopolymers and Cell, 2015)
Aim. To evaluate a possible role of a novel c.A212G substitution in the PUS3 gene at intellectual disability (ID). Methods. The observed group consisted of the ID Ukrainian family members (parents and two affected children) and the control group – of 300 healthy individuals from general population of Ukraine. Sanger sequencing of the PUS3 gene exon 1 was performed for the family members. Polymorphic variants of c.A212G were analyzed using ARMS PCR. The homology models of wild type and p.Y71C mutant catalytic domains of human Pus3 were generated using the crystal structure of the human Pus1 catalytic domain (PDB ID: 4NZ6) as a template. Results. It was shown that the father of the affected siblings was the c.A212G substitution heterozygous carrier whereas the mother was a wild type allele homozygote, and the exom sequencing result was confirmed – the affected children are 212G homozygotes. We supposed de novo mutation in the maternal germ line. A low frequency of 212G allele (0.0017) was shown in the population of Ukraine. Homology modelling of the wild type and p.Y71C mutant catalytic domain of human Pus3 revealed that substitution p.Y71C is located in close proximity to its active site. Conclusions. The absence of hypoproteinemia in our patients, homozygous for the 212C allele allows us to assume that the mutation c.A212G PUS3 is rather neutral and cannot be the major cause of ID. However, considering a low frequency of the 212G allele in the population and close localization of p.Y71C substitution to the active site of hPus3 we cannot exclude that the c.A212G mutation in PUS3 may be a modifier for some pathologies including syndromic ID.